Enhancing activated carbon supercapacitor electrodes using sputtered Cu-doped BiFeO3 thin films - Nantawat Tanapongpisit; Suchunya Wongprasod; Peerawat Laohana; Somchai Sonsupap; Jessada Khajonrit; Supansa Musikajaroen; Unchista Wongpratat; Benjaporn Yotburut; Santi Maensiri; Worawat Meevasana; Wittawat Saenrang (Scientific Reports, 2024)
Abstract This work describes the fabrication of a composite supercapacitor electrode made of Cu-doped BiFeO $$_3$$ 3 (Cu-BFO) films on an activated carbon (AC) electrode using radio-frequency (RF) magnetron sputtering. To prevent exfoliation of Cu-BFO and AC upon immersion in an electrolyte, the nickel foam sandwiching electrode technique was introduced. The Cu-BFO films significantly enhanced electrochemical properties, increasing specific capacitance by up to 151% compared to that of an AC electrode. This was attributed to Faradaic reactions and specific surface area in the Cu-BFO/AC electrode. The highest specific capacitance achieved was 169 F $$\hbox {g}^{-1}$$ g - 1 at 0.5 A $$\hbox {g}^{-1}$$ g - 1 , and cycling stability retention was 93.12% after 500 cycles. However, the remaining percentage of the specific capacitance decreased differently with increasing thickness, which is also discussed. Furthermore, an asymmetric supercapacitor using Cu-BFO/AC and AC electrodes demonstrated a high energy density of 4.71 Wh $$\hbox {kg}^{-1}$$ kg - 1 , power density of 2.66 kW $$\hbox {kg}^{-1}$$ kg - 1 , and over 90% retention after 1000 cycles, highlighting its durability. The uniform RF magnetron sputtering deposition is vital for mass production. Combined with impressive retention in asymmetric supercapacitors, this scalability suggests a promising pathway for large-scale manufacturing. Consequently, this work could pave the way for the large-scale production of supercapacitors.